Leveraging type 1 diabetes human genetic and genomic data in the T1D knowledge portal - Kudtarkar, Parul; Costanzo, Maria C.; Sun, Ying; Jang, Dongkeun; Koesterer, Ryan; Mychaleckyj, Josyf C.; Nayak, Uma; Onengut-Gumuscu, Suna; Rich, Stephen S.; Flannick, Jason A.; Gaulton, Kyle J.; Burtt, Noël P. (PLoS biology, 2023)
To address the challenge of translating genetic discoveries for type 1 diabetes (T1D) into mechanistic insight, we have developed the T1D Knowledge Portal (T1DKP), an open-access resource for hypothesis development and target discovery in T1D.